The ALPK1 pathway drives the inflammatory response to Campylobacter jejuni in human intestinal epithelial cells - Cui, Jiannan; Duizer, Coco; Bouwman, Lieneke I.; van Rooijen, Kristel S.; Voogdt, Carlos G. P.; van Putten, Jos P. M.; de Zoete, Marcel R. (PLoS pathogens, 2021)
The Gram-negative bacterium Campylobacter jejuni is a major cause of foodborne disease in humans. After infection, C . jejuni rapidly colonizes the mucus layer of the small and large intestine and induces a potent pro-inflammatory response characterized by the production of a large repertoire of cytokines, chemokines, and innate effector molecules, resulting in (bloody) diarrhea. The virulence mechanisms by which C . jejuni causes this intestinal response are still largely unknown. Here we show that C . jejuni releases a potent pro-inflammatory compound into its environment, which activates an NF-κB-mediated pro-inflammatory response including the induction of CXCL8 , CXCL2 , TNFAIP2 and PTGS2 . This response was dependent on a functional ALPK1 receptor and independent of Toll-like Receptor and Nod-like Receptor signaling. Chemical characterization, inactivation of the heptose-biosynthesis pathway by the deletion of the hldE gene and in vitro engineering identified the released factor as the LOS-intermediate ADP-heptose and/or related heptose phosphates. During C . jejuni infection of intestinal cells, the ALPK1-NF-κB axis was potently activated by released heptose metabolites without the need for a type III or type IV injection machinery. Our results classify ADP-heptose and/or related heptose phosphates as a major virulence factor of C . jejuni that may play an important role during Campylobacter infection in humans.